Manufacturing method for printed circuit board

The described method for forming vapor deposition layers on ceramic substrates and aligning metal sheets in specific ratios addresses the challenge of weak joint forces in multi-layered circuit boards, achieving strong bonds and cost-effective production.

JP7625710B2Active Publication Date: 2025-02-03LX SEMICON CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023544425
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-21
Filing Date
2022-01-21
Publication Date
2025-02-03
Estimated Expiration
2042-01-21

AI Technical Summary

Technical Problem

Existing methods for manufacturing multi-layered print circuit boards face challenges in achieving strong layer joint forces while minimizing production costs, particularly due to thermal expansion mismatches between ceramic substrates and metal sheets, leading to peeling issues under thermal impact.

Method used

A manufacturing method involving the formation of vapor deposition layers on ceramic substrates, followed by precise alignment and heat-pressing of metal sheets, ensures a robust bond between ceramic substrates and metal sheets, utilizing specific area ratios and materials like silicon nitride and copper sheets to enhance joint strength.

Benefits of technology

The method results in a print circuit substrate with enhanced joint strength, reducing production costs and minimizing peeling under thermal stress, while allowing for efficient production of multiple circuit boards in parallel, thus optimizing resource utilization and reducing labor costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625710000004
    Figure 0007625710000004
  • Figure 0007625710000005
    Figure 0007625710000005
  • Figure 0007625710000006
    Figure 0007625710000006
Patent Text Reader

Abstract

The present application relates to a method for manufacturing a printed circuit board, and more particularly to a method for manufacturing a printed circuit board having excellent bonding strength between a ceramic substrate and a metal sheet, and reducing the manufacturing cost.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to a method for manufacturing a substrate for a printed circuit board. More specifically, the present application relates to a method for manufacturing a substrate for a printed circuit board, which can reduce production costs and improve interlayer adhesion strength forming the substrate. [Background technology]

[0002] As electronic devices become smaller, lighter, and more functional, the number of applications for build-up printed circuit boards, particularly in small devices, has increased, leading to an increased demand for multilayer printed circuit boards.

[0003] Multilayer printed circuit boards are capable of two-dimensional and three-dimensional wiring, and are particularly advantageous in the industrial electronics field in that they not only increase the integration density of functional elements (e.g., ICs (integrated circuits) or LSIs (large scale integration)), but also in making electronic devices smaller, lighter, and more functional, integrating electrical functions structurally, shortening assembly times, and reducing costs.

[0004] A printed circuit board can be manufactured by bonding metal sheets, such as copper sheets, to both opposing sides of a ceramic substrate, such as alumina (Al2O3), aluminum nitride (AlN), silicon nitride (Si3N4), or the like.

[0005] Bonding methods for printed circuit boards can be broadly divided into three types: active metal brazing (AMB), which uses a paste mainly composed of Ag; direct bonding, which uses the oxide layer of the ceramic substrate for bonding; and diffusion bonding, which uses metal deposition and a diffusion reaction.

[0006] Among these, the active metal method has the problem of Ag diffusing to the edges when the power semiconductor module is in operation, while the direct bonding method has the problem of reduced thermal conductivity due to an oxide layer.On the other hand, the diffusion bonding method can form a thin deposition layer several hundred nanometers thick through a solid-state reaction, and has the advantage that it uses an extremely small amount of metals such as Ag compared to the active metal method, and has excellent bonding strength, making it possible to manufacture printed circuit boards with excellent thermal shock properties.

[0007] Meanwhile, printed circuit boards are repeatedly exposed to heat due to the application of voltage, and are exposed to thermal shock conditions due to changes in the surrounding environment. At this time, thermal stress occurs because the thermal expansion coefficients of the ceramic substrate and the metal sheet (e.g., copper sheet) are different, and peeling is likely to occur due to repeated thermal shock.

[0008] Therefore, there is a need for a technique for manufacturing printed circuit boards having strong interlayer bonding strength while reducing production costs. Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present application is to provide a method for manufacturing a printed circuit board that can reduce production costs.

[0010] Another object of the present application is to provide a printed circuit board having a strong interlayer bonding strength so that peeling does not occur even in a thermal shock environment.

[0011] The above and other objects of the present application can be alleviated by the present application as described in detail below. [Means for solving the problem]

[0012] In order to achieve the above object, in one aspect, the present embodiment is a casing having an upper surface and a lower surface facing each other, the areas of which are S A A ceramic substrate (a) having the area S Aa first step of forming a deposition layer on each of the upper and lower surfaces of a ceramic substrate having an area S A Area S is 1.5 times larger than B A second step of preparing an upper metal sheet (B) and a lower metal sheet (B') having a surface of each of the upper metal sheet (B) and the lower metal sheet (B') facing each other with a surface area S B a third step of arranging the metal sheets (B, B') and the two or more ceramic substrates (A) between one side of the upper and lower metal sheets (B, B') such that the two or more ceramic substrates (A) are positioned parallel to one another in a plane; and a fourth step of hot pressing the upper and lower metal sheets (B, B') to bond the metal sheets (B, B') and the ceramic substrates (A) via the upper and lower deposition layers. Effect of the Invention

[0013] According to the present application, a printed circuit board having excellent bonding strength between a ceramic substrate and a metal sheet can be manufactured, and the manufacturing cost can be reduced. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a cross-sectional view showing a ceramic substrate 100, a deposition layer 200, and a metal sheet 300 in connection with a manufacturing process of a printed circuit board according to an embodiment of the present application. [Diagram 2] FIG. 2 is a schematic diagram showing the arrangement relationship between the metal sheet and the ceramic substrate in the prior art and in the present application. [Diagram 3] FIG. 3 is a cross-sectional view of a printed circuit board including a ceramic substrate 100, a bonding layer 200a, and a metal sheet 300 according to an embodiment of the present application. [Figure 4] FIG. 4 is a scanning electron microscope (SEM) image of a cross section of a ceramic substrate and a deposition layer formed according to an embodiment of the present application. [Diagram 5]FIG. 5 is a scanning electron microscope (SEM) image of a cross section of a ceramic substrate, a bonding layer, and a metal sheet formed according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present application will now be described in detail with reference to the accompanying drawings relating to specific examples of the present application.

[0016] For clarity of explanation, parts not related to the explanation are omitted in the drawings, and the same reference numerals are used for the same or similar components throughout the specification. In addition, the size and thickness of each component shown in the drawings are arbitrarily enlarged or reduced for convenience of explanation, and therefore the size and thickness of the components of the present application are not necessarily limited to those shown in the drawings.

[0017] In this specification, the term "above" when used in relation to a position between structures is used in a sense corresponding to "on" or "upper" and, unless otherwise specifically stated, can mean when the structure having the position in question is directly adjacent to and above the other structure, or when there is another structure therebetween.

[0018] In this specification, unless otherwise specifically defined, "area" may refer to the area in which each component is visible when the component is observed from above or below in a direction parallel to the normal direction of its surface, for example, the orthogonal projection area. Therefore, an increase or decrease in the actual area due to irregularities, etc., of the component to be compared or the area of ​​which is referred to or compared is not taken into consideration.

[0019] Throughout this specification, the terms "comprise" and "have" mean that other elements may be further included, unless otherwise specifically stated.

[0020] In this specification, the terms "step" and "process" may be used interchangeably.

[0021] In one embodiment of the present application, the present application relates to a method for manufacturing a printed circuit board, which can be carried out by manufacturing a laminate having a predetermined structure and hot pressing the laminate.

[0022] For example, as shown in FIG. 1, the manufacturing method may include preparing a ceramic substrate 100, forming deposition layers 200 on two opposing surfaces of the ceramic substrate 100, placing a metal sheet 300 on the deposition layer 200, and hot pressing the metal sheet from the outside of the metal sheet to bond the ceramic substrate 100 and the metal sheet 300 together.

[0023] According to the embodiment of the present application relating to the manufacturing process, the area of ​​the ceramic substrate and the metal sheet and / or the stacking position before bonding can be adjusted, thereby reducing production costs. In addition, according to the embodiment of the present application, the deposition components and their contents can be adjusted to provide excellent bonding strength between the ceramic substrate and the metal sheet.

[0024] Specifically, the method comprises: The areas of the upper and lower surfaces facing each other are S A A ceramic substrate (a) having the area S A A first step of forming deposition layers on the upper and lower surfaces of a ceramic substrate having the above structure, thereby manufacturing a ceramic substrate (A) having an upper deposition layer and a lower deposition layer formed on the upper and lower surfaces facing each other, respectively; The area S A Area S is 1.5 times larger than B A second step of preparing an upper metal sheet (B) and a lower metal sheet (B') having one side of The opposing area S of the upper metal sheet (B) and the lower metal sheet (B') B a third step of arranging the metal sheet (B, B') and the two or more ceramic substrates (A) between the first and second surfaces of the metal sheet (B, B') so that the two or more ceramic substrates (A) are positioned parallel to one another in a plane; and a fourth step of hot pressing the upper and lower metal sheets (B, B') to bond the metal sheets (B, B') to the ceramic substrate (A) via the upper and lower deposition layers.

[0025] Each step and the components used in each step are described in more detail below.

[0026] The ceramic substrate (a) mentioned in relation to the first step is a substrate for printed circuits that can provide a type of heat dissipation performance. As long as it can provide heat dissipation performance, the type of components used in the ceramic substrate is not particularly limited.

[0027] In one embodiment, the ceramic substrate (a) may include at least one of Si3N4, AlN, and Al2O3. Specifically, the ceramic substrate (a) may include at least one selected from Si3N4 and AlN.

[0028] In one example, the ceramic substrate (a) may include at least Si3N4. The flexural strength of Si3N4 is generally in the range of 600 to 1,400 MPa, which is the best level among ceramics. In addition, Si3N4 has a flexural strength of about 3.2×10 -6 / K, it is a material that can be used at high temperatures. In addition, Si3N4 has a thermal expansion coefficient of about 3.2 g / cm 3 It has a density of 1000 nm, a thermal conductivity in the range of 30~178 W / (m K), and high thermal shock resistance in the range of 800~1000 K. These characteristics make Si3N4 an effective heat dissipation material. Therefore, a printed circuit board manufactured using a ceramic substrate containing Si3N4 can function as a circuit board with excellent heat dissipation performance.

[0029] The process and method for producing the ceramic substrate (a) are not particularly limited.

[0030] For example, the ceramic substrate (a) is manufactured through a process of preparing a slurry containing ceramic powder, a tape casting process, a punching process, a burnout process, a sintering process, and the like.

[0031] The slurry preparation step may be a step of preparing a slurry by mixing a powder with an organic solvent, a sintering aid, a plasticizer, and a dispersant. In this case, the ceramic powder may include at least one of Si3N4 powder, AlN powder, and Al2O3 powder. The powder may be prepared using a ball mill, etc., and the average particle size of the powder is preferably 0.8 μm or less. In this case, the average particle size refers to the size of a particle that is the median in the particle size distribution of n particles used. For example, when the sizes of 100 particles are arranged in order from largest to smallest, the size of the particle that is the 50th largest may be called the average particle size.

[0032] In one example, when Si3N4 powder is used, the Si3N4 powder may include at least one of β-Si3N4 and α-Si3N4. When β-Si3N4 and α-Si3N4 are mixed and used as the Si3N4 powder, the content (e.g., weight) ratio between the mixed components is not particularly limited.

[0033] The type of the organic solvent is not particularly limited, and for example, one or more selected from the group consisting of toluene, benzene, xylene, methyl ethyl ketone (MEK), propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), ethanol, butanol, and methanol can be used.

[0034] The type of the sintering aid is not particularly limited, and for example, rare earth element oxides, alkaline earth metal oxides, and combinations thereof can be used.

[0035] The type of the plasticizer is not particularly limited. For example, one or more selected from the group consisting of di-2-ethylhexyl phthalate, di-n-butyl phthalate, butyl phthalyl butyl glycolate, polyethylene glycol, and dioctyl phthalate can be used as the plasticizer.

[0036] The dispersant is not particularly limited, and for example, one or more selected from the group consisting of polyester-based dispersants, polyacrylate-based dispersants, polyurethane-based dispersants, and polyether-based dispersants can be used.

[0037] The tape casting process may be a process in which the slurry is applied to a polymer film at a certain thickness and then passed through a drying chamber to produce a ceramic tape, such as a Si3N4 tape.

[0038] The punching process may be a process of pressing and cutting the ceramic tape to manufacture a ceramic green sheet, such as a Si3N4 green sheet.

[0039] The burnout process may be a process performed by heat treating the green sheet (e.g., Si3N4 green sheet). Specifically, the burnout process may be performed by heat treatment in air or nitrogen atmosphere. Specific heat treatment conditions are not particularly limited, but the heat treatment may be performed, for example, at a temperature in the range of 400 to 800°C for 6 to 18 hours.

[0040] The sintering process may be a process of sintering the degreased green sheet (e.g., Si3N4 green sheet). The sintering process may be performed by gas pressure sintering (GPS). Specific gas pressure sintering conditions are not particularly limited, but for example, a gas pressure sintering furnace having a temperature in the range of 1600 to 2000°C, a nitrogen atmosphere, and 8 to 12 atm conditions may be used in the sintering process.

[0041] After the sintering, post-processing including grinding is performed to produce a ceramic substrate (a) containing one or more of Si3N4, AlN, and Al2O3.

[0042] The ceramic substrate (a) manufactured through the above-mentioned process has an upper surface and a lower surface facing each other with an area of ​​S. A In this case, the expressions "upper surface" and "lower surface" are terms for explaining the relative positions of the two surfaces facing each other, and do not mean absolute positions.

[0043] The shape of the ceramic substrate and the upper and lower surfaces forming the ceramic substrate are not particularly limited. For example, the ceramic substrate may be a plate, and the upper and lower surfaces may have a polygonal (e.g., rectangular) or circular shape.

[0044] In one example, the shape of the upper and lower surfaces of the ceramic substrate (a) facing each other (or the area S A The shape in which the square is visible may have a rectangular shape. Although not particularly limited, the area S of the square shape A The size of the ceramic substrate (a) having the above structure may be, for example, 150 to 220 mm in width and 100 to 160 mm in length.

[0045] Although not particularly limited, the thickness of the ceramic substrate may be in the range of 0.05 to 2.0 mm.

[0046] According to a specific example of the present application, a deposition layer is formed on each of the upper and lower surfaces of the ceramic substrate (a) that face each other. As described above, the upper and lower surfaces on which the deposition layer is formed have an area S A has.

[0047] The deposition layer is capable of bonding a metal sheet and a ceramic substrate after hot pressing as described below.

[0048] The deposition (process) for forming the deposition layer is not particularly limited, and may be any known deposition method such as sputtering for physical vapor deposition (PVD) or chemical vapor deposition (CVD).

[0049] Although not particularly limited, the area on the ceramic substrate on which the deposition layer is formed is A For example, the deposition layers formed on the upper and lower surfaces of the ceramic substrate (a) may have the same area as the upper and lower surfaces.

[0050] In one example, the deposition layers formed on the upper and lower surfaces of the ceramic substrate (a) may have the same area and shape as the upper and lower surfaces. In this case, the same area and shape includes not only the case where the areas and shapes are all the same, but also the case where the geometric shapes of the areas are similar to each other even if the sizes of the areas are different (similar shapes).

[0051] In one example, the deposition layers formed on the upper and lower surfaces of the ceramic substrate (a) may have the same area and shape as the upper and lower surfaces on which they are formed.

[0052] The type of components used to form the deposition layer is not particularly limited. For example, the deposition layer may include one or more of Ag and Ti.

[0053] In one embodiment, the deposition layer may include Ag and Ti. Specifically, the deposition amount of Ag per unit area in the deposition layer may be 3.50 to 6.10 g / m 2 and the deposition amount of Ti per unit area is 0.61 to 1.30 g / m 2 In this case, the "amount of deposition per unit area" refers to the area (m 2 It can mean the content (g) of the deposition component (Ti or Ag) relative to the total weight of the deposited layer. When the components and deposition amount of the deposition layer are adjusted as above, the bonding strength can be improved.

[0054] In one embodiment, the deposition amount of Ti contained in the deposition layer per unit area is 0.61 to 1.30 g / m 2 In order to provide a stronger bonding strength between the metal sheet and the ceramic substrate, the deposition amount of Ti per unit area may be in the range of 1.02 to 1.30 g / m. 2 Specifically, the range is 1.04 to 1.20 g / m 2 It is more preferable that the range is .

[0055] In one embodiment, the deposition amount of Ag contained in the deposition layer per unit area is 3.50 to 6.10 g / m 2 In order to provide a stronger adhesive strength between the metal sheet and the ceramic substrate, the deposition amount of Ag per unit area may be in the range of 4.00 to 4.60 g / m. 2 It is preferable that the range is 100%.

[0056] As a result of the deposition layers being formed on the upper and lower surfaces of the ceramic substrates (a) facing each other as described above, a ceramic substrate (A) having an upper deposition layer and a lower deposition layer formed on the upper and lower surfaces facing each other, respectively, is manufactured. In this case, the upper deposition layer is a deposition layer formed on the upper surface, and the lower deposition layer is a deposition layer formed on the lower surface.

[0057] As described in relation to the third and fourth steps below, the upper deposition layer is disposed opposite the upper metal sheet (B), and the lower deposition layer is disposed opposite the lower metal sheet (B'), and through subsequent hot pressing, these deposition layers can function as a medium for bonding the metal sheets (B, B') and the ceramic substrate (A).

[0058] In one example, at least one of the upper deposition layer and the lower deposition layer may include a first deposition layer and a second deposition layer having different components. Specifically, the first deposition layer may include Ti, and the second deposition layer may include Ag. In this case, the first deposition layer means a layer closer to the ceramic substrate (a) than the second deposition layer. That is, the first deposition layer may mean a layer formed on the upper and lower surfaces of the ceramic substrate, and the second deposition layer may mean a layer formed on the first deposition layer. For example, as shown in FIG. 1, a first deposition layer 210 is formed on a ceramic substrate 100, and a second deposition layer 220 is formed on the first deposition layer.

[0059] Regarding the first and second deposition layers, the deposition (process) of the method may include forming (depositing) a first deposition layer containing Ti on the upper and lower surfaces of the ceramic substrate (a), respectively, and forming (depositing) a second deposition layer containing Ag on the first layer. As a result, a laminate (i.e., ceramic substrate (A)) in which the second deposition layer 220, the first deposition layer 210, the ceramic substrate 100, the first deposition layer 210, and the second deposition layer 220 are sequentially positioned is manufactured, as shown in FIG.

[0060] In one example, the first deposition layer may refer to a deposition layer formed directly on the upper and lower surfaces of the ceramic substrate.

[0061] In one example, the second deposition layer may refer to a deposition layer formed directly on the first layer.

[0062] Although not particularly limited, the area where the first deposition layer and the second deposition layer are formed on the ceramic substrate is AIt can have a size of 50% to 100% of the area.

[0063] In one example, the first deposition layer may have the same area and shape as the upper and lower surfaces.

[0064] In one example, the first deposition layer may have the same area and shape as the upper and lower surfaces.

[0065] In one example, the second deposition layer may have the same area and shape as the first deposition layer.

[0066] In one example, the second deposition layer may have the same area and shape as the first deposition layer.

[0067] In one embodiment, the deposition amount of Ti contained in the first deposition layer per unit area is 0.61 to 1.30 g / m 2 Specifically, the deposition amount of Ti per unit area can be in the range of 1.02 to 1.30 g / m 2 More specifically, the range may be 1.04 to 1.20 g / m 2 In view of providing a stronger bonding strength between the metal sheet and the ceramic substrate, it is preferable that the thickness of the ceramic substrate is in the range of 100 nm to 150 nm.

[0068] In one embodiment, the deposition amount of Ag contained in the second deposition layer per unit area is 3.50 to 6.10 g / m 2 Specifically, the deposition amount of Ag per unit area can be in the range of 4.00 to 4.60 g / m 2 In view of providing a stronger bonding strength between the metal sheet and the ceramic substrate, it is preferable that the thickness of the ceramic substrate is in the range of 100 nm to 150 nm.

[0069] The second step is to prepare an upper metal sheet (B) and a lower metal sheet (B') to be placed on the upper and lower deposition layers. For example, as shown in FIG. 1, two metal sheets 300 are prepared to be placed on each deposition layer 200.

[0070] In order to explain the manner in which the third and fourth steps are performed, it has been described that the second step of preparing a metal sheet (B) is performed after the first step of manufacturing a ceramic substrate (A). However, changing the order of the first and second steps is an obvious modification that can be made by a person skilled in the art.

[0071] The metal sheets (B, B') used in the specific examples of the present application have one surface with a predetermined area. Specifically, the one surface of the metal sheets (B, B') has an area S of the upper and lower surfaces of the ceramic substrate. A Larger area S B More specifically, the area S of one surface of the metal sheet (B) B is the area S A As explained below, the area S B The metal sheet is arranged so that two or more ceramic substrates (A) are aligned parallel to the plane. B It can be arranged on one side of the area, thereby reducing production costs.

[0072] In one example, the area (S B ) is the area (S A ) or less, such as 6.0 times, 5.0 times, 4.0 times, 3.0 times, or 2.5 times. More specifically, the area (S B ) is the area (S A ) or more, 1.6 times or more, 1.7 times or more, 1.8 times or more, 1.9 times or more, or 2.0 times or more, and may be 2.4 times or less, 2.3 times or less, 2.2 times or less, or 2.1 times or less. B If the gap is too large, the etching solution is difficult to wash off, and the etching solution may accumulate on the substrate (residual etching solution) or the etching may become non-uniform.

[0073] In one example, the shape of the metal sheet may be the same as the shape of the ceramic substrate.

[0074] In the specific example of the present application, the area S AThe upper and lower surfaces of the ceramic substrate are B When one surface of the metal sheet (B, B') has a quadrangular shape, the size of the metal sheet (B, B') may be, for example, 250 to 300 mm in width and 160 to 210 mm in length.

[0075] In addition, although not particularly limited, the thickness of the metal sheets (B, B') may be in the range of 0.05 to 3.0 mm.

[0076] There is no particular limitation on the type of metal contained in the metal sheet (B). For example, the metal sheet (B) may contain one or more selected from Cu, Al, Ni, and Fe.

[0077] The third step is to arrange the ceramic substrate (A) and the metal sheets (B, B') so that the two or more ceramic substrates (A) are positioned on the metal sheets parallel to one another in a plane. According to a specific example of the present application, the two or more ceramic substrates (A) used may have the same size and shape.

[0078] Specifically, the third step is to measure the mutually opposing area S of the upper metal sheet (B) and the lower metal sheet (B'). B and arranging the metal sheets (B, B') and the two or more ceramic substrates (A) between the first and second surfaces of the metal sheets (B, B') so that the two or more ceramic substrates (A) are positioned side by side parallel to a plane.

[0079] In relation to the above three steps, the fact that two or more ceramic substrates (A) are arranged parallel to one another means that the two or more ceramic substrates (A) to be placed on the metal sheets (B, B') do not overlap each other, i.e., are not stacked. Therefore, the two or more ceramic substrates (A) to be placed on the metal sheets through the third step do not have an overlapping area with each other, and the overlapping area between these ceramic substrates (A) is 0 (zero).

[0080] By the arrangement of the three steps, the upper metal sheet (B) has the area S B The upper metal sheet (B) is positioned so that one side of the upper metal sheet (B) having the area S faces the upper deposition layer (of all the ceramic substrates, if the ceramic substrate is two or more). B The lower metal sheet (B') is positioned so that one side of the lower metal sheet (B') having the above structure faces the lower deposition layer (of all of the two or more ceramic substrates). The subsequent fourth step of hot pressing bonds the two or more ceramic substrates (A) arranged parallel to one another in a plane between the metal sheets (B, B') to the metal sheets (B, B') (through the upper and lower deposition layers). For example, the upper metal sheet (B) is bonded to all of the upper surfaces of the two or more ceramic substrates through the upper deposition layer, and the lower metal sheet (B') is bonded to all of the lower surfaces of the two or more ceramic substrates through the lower deposition layer.

[0081] In one embodiment, the upper deposition layer has an area S B The substrate is disposed so as to be in direct contact with or directly opposite the surface which is the substrate.

[0082] In one embodiment, the lower deposition layer has an area S B The substrate is disposed so as to be in direct contact with or directly opposite the surface which is the substrate.

[0083] In one embodiment, the three steps are performed in relation to the arrangement of the metal sheets (B, B') and the ceramic substrate (A) such that the area is S B The overlapping area between one surface of the metal sheet and the two or more ceramic substrates (A) is less than the total area (S T = n × S A(where n is a natural number of 2 or more and means the number of ceramic substrates located between the metal sheets (B, B')) may be 70% or more. For example, the overlapping area may be 75% or more, 80% or more, 85% or more, 90% or more, or 95% or more of the total area of ​​the ceramic substrate (A) located between the upper metal sheet (B) and the lower metal sheet (B').

[0084] When the laminate arranged as described above is subjected to hot pressing as described below, two or more ceramic substrates (A) positioned parallel to each other on the same plane between the upper metal sheet (B) and the lower metal sheet (B') are bonded to the upper metal sheet (B) and the lower metal sheet (B') via the deposition layer or a structure derived therefrom.

[0085] In the prior art, it was common to bond a ceramic substrate and a metal sheet having the same level of area. However, in this application, the area of ​​the ceramic substrate (S A ) to find its area (S B ) is at least 1.5 times larger than that of the substrate (see FIG. 2). In the manufacture of printed circuit boards, etching is performed. When two or more ceramic substrates are subjected to one etching process by the above arrangement, the effective area increases, more etched pieces can be produced, and at the same time, the waste portion is reduced. In the conventional technology, substrates to be etched are fed one by one into the line for the etching process, but in the above arrangement, two substrates can be fed into the etching line compared to the conventional technology, which reduces the process time and associated costs (e.g., labor costs, etc.). In addition, in the printing process, a process of attaching a protective film to the part that should not be etched is further performed, and as described above, the film is attached to the area of ​​two substrates, which reduces the time and costs (e.g., labor costs, etc.) for associated processes. In this way, the present application can reduce production costs.

[0086] In one example, with regard to the arrangement of the metal sheets (B, B') and the ceramic substrates (A), the at least two ceramic substrates (A) are arranged on one side of the metal sheet (B, B') with a predetermined distance from the edge of the metal sheet. When the substrates are spaced apart from the edge of the metal sheet, the portion that is clamped by a jig during processing can be secured, and the distance between two or more ceramic substrates becomes closer, reducing dead zones and preventing waste of raw materials.

[0087] According to a specific example of the present application, the non-bonded laminate obtained through the above three steps, i.e., a non-bonded laminate having a structure of metal sheet (B) / two or more ceramic substrates (A) (positioned parallel to one another in a plane) / metal sheet (B'), can be referred to as a set of master cards (MC).

[0088] In one example, the method may further include a step of manufacturing a stack of the master cards. At this time, an anti-adhesion sheet made of a different material may be inserted between each set to prevent adhesion between the metal sheets 300. The anti-adhesion sheet may include, for example, graphite. Although not particularly limited, known bonding techniques or bonding materials may be used to form the stack.

[0089] The fourth step is a step of hot pressing the upper and lower metal sheets (B, B') positioned on the deposition layer to bond the ceramic substrate (A) to the upper and lower metal sheets (B, B').

[0090] The fourth step can be performed by hot pressing the metal sheets (B, B') in the direction of the ceramic substrate (A) at a temperature of 450 to 1,300°C and a pressure of 1 to 25 MPa. Although not particularly limited, the hot pressing can be performed for about 10 -1 ~10 -5 The process may be performed in a vacuum atmosphere of 1000 torr.

[0091] For example, the lower limit of the temperature during bonding may be 500° C. or more, 600° C. or more, 700° C. or more, or 800° C. or more, and the upper limit may be, for example, 1050° C. or less, 1000° C. or less, 950° C. or less, or 900° C. or less.

[0092] For example, the lower limit of the pressure during bonding may be, for example, 5 MPa or more or 10 MPa or more, and the upper limit may be, for example, 20 MPa or less or 15 MPa or less.

[0093] The metal sheets (B, B') and the ceramic substrate (A) may be bonded to each other by the deposition layer (or a layer containing a component derived from the deposition layer) through the hot pressing. For example, FIG. 3 is a schematic diagram showing a cross-section of a substrate or a laminate obtained through a bonding step according to an embodiment of the present application. As shown in FIG. 3, the laminate obtained after bonding has a structure in which a bonding layer 200a and a metal sheet 300 are sequentially formed on the upper and lower surfaces of the ceramic substrate 100, respectively. In this case, the bonding layer 200a is a deposition layer or a layer derived from a deposition layer that has been subjected to a bonding step.

[0094] 1 and 3 to 5, hot pressing causes diffusion between materials contained in the ceramic substrate 100, deposition layer 200, and metal sheet 300. For example, when the first deposition layer 210 contains Ti and the ceramic substrate (a) 100 contains Si3N4, a reaction occurs between Ti and Si3N4 as shown in Reaction Scheme 1 below.

[0095] [Reaction Scheme 1] 4Ti+Si3N4->3Si+4TiN

[0096] That is, the material contained in the deposition layer 200 reacts with the material contained in the ceramic substrate 100 by the hot pressing to form the bonding layer 200a, and the bonding layer 200a may include TiN.

[0097] The bonding layer 200a according to this embodiment is a layer containing TiN, and can act as a strong bonding medium layer between the ceramic substrate 100 and the metal sheet 300. That is, the bonding layer 200a is formed by the diffusion bonding method, thereby bonding the ceramic substrate 100 and the metal sheet 300.

[0098] As described above, the deposition amount of Ag contained in the second deposition layer 220 in the deposition step is 3.50 to 6.10 g / m 2 More specifically, the deposition amount of Ag contained in the second deposition layer 220 per unit area may be in the range of, for example, 4.00 to 4.60 g / m 2 In the case where layers including different materials are bonded to each other, stress transfer occurs in the layer including the material having a relatively weak strength, and interlayer debonding easily occurs. Therefore, increasing the strength of the layer including the material having a relatively weak strength is more effective in improving the bonding strength in the bonding between layers including different materials. For example, Ag included in the second deposition layer 220 can diffuse toward the metal sheet 300 including Cu during the hot pressing to compensate for the weak strength of the metal sheet 300 at the interface. Based on the above principle, Ag included in the second deposition layer 220 can improve the bonding strength between the ceramic substrate 100 and the metal sheet 300. In addition, Ag included in the second deposition layer 220 can form a liquid phase consisting of a ternary system of Cu-Ti-Ag together with Ti included in the first deposition layer 210 and Cu included in the metal sheet 300 to improve wettability and support the promotion of reaction layer formation.

[0099] If the deposition amount of Ag per unit area included in the second deposition layer 220 is less than the above range, the strength of the metal sheet 300 cannot be sufficiently increased, and the bonding strength between the ceramic substrate 100 and the metal sheet 300 is deteriorated. If the deposition amount of Ag per unit area included in the second deposition layer 220 exceeds the above range, more Ag than necessary is deposited to form undiffused Ag remnants, which may result in a decrease in the bonding strength between the ceramic substrate 100 and the metal sheet 300.

[0100] The deposition amount of Ti contained in the first deposition layer 210 per unit area is 0.61 to 1.30 g / m 2 Specifically, for example, the range is 1.02 to 1.30 g / m 2 The range is preferably 1.04 to 1.20 g / m 2 It is more preferable that the deposition amount of Ti per unit area is in the range of 100 to 300. The deposition amount of Ti per unit area is related to the thickness of the bonding layer 200a, and affects the bonding strength between the ceramic substrate 100 and the metal sheet 300.

[0101] If the deposition amount per unit area of ​​Ti included in the first deposition layer 210 is less than the above range, the thickness of the bonding layer 200a becomes insufficient, and the bonding strength between the ceramic substrate 100 and the metal sheet 300 becomes poor. For example, as in the comparative example below, the bonding strength between the ceramic substrate 100 and the metal sheet 300 becomes less than 9 N / mm. If the deposition amount per unit area of ​​Ti included in the first deposition layer 210 exceeds the above range, the deposition amount reaches a saturation value, the increase in bonding strength is small, and raw materials are wasted.

[0102] As described above, in the method for producing a printed circuit board according to the present application, the deposition amount of Ag per unit area is 3.50 to 6.10 g / m 2 The deposition amount of Ti per unit area was adjusted to 0.61 to 1.30 g / m 2 By adjusting the temperature to within the above range, a printed circuit board having excellent interlayer bonding strength can be manufactured. As a result, the printed circuit board manufactured as above does not peel off or peeling is significantly suppressed even when exposed to a repeated thermal shock environment.

[0103] In one example, the method may further include an etching step for the metal sheets (B, B'). Specifically, after the bonding step, a printed circuit board is manufactured by performing a resist printing process, an etching process, a plating process, etc., on the bonded ceramic substrate 100 and / or the metal sheet 300.

[0104] In Figure 2, the red arrow indicates the direction of hot pressing, and MC (master card) indicates a laminate in the form of metal sheet / ceramic substrate / metal sheet. The present invention, in which two ceramic substrates are arranged in parallel on a flat surface and then bonded, has a higher production volume and lower etching cost than the conventional technology.

[0105] 4 is a cross-sectional image after the deposition step and before the bonding step. It can be seen from FIG 4 that a first layer 210 containing Ti and a second layer 220 containing Ag were formed on a ceramic substrate 100.

[0106] 5 is a cross-sectional photograph after the bonding step. From FIG 5, it can be seen that a bonding layer 200a is formed after the bonding step by the diffusion bonding method, and the ceramic substrate 100 and the metal sheet 300 are bonded to each other.

[0107] The functions and effects of the present invention will be described in more detail below with reference to specific examples of the present invention, however, these are presented as examples of the present invention and do not limit the scope of the invention in any way.

[0108] Manufacturing example (manufacturing of ceramic substrate (a))

[0109] A ball mill is used to produce Si3N4 powder with an average particle size of 0.8μm or less. Organic solvents (e.g., toluene, methanol, ethanol), sintering aids (e.g., Y2O3, MgO), plasticizers (e.g., dioctyl phosphate (DOP), polyethylen glycol (PEG)), and dispersants (e.g., BYK-111) are added to the Si3N4 powder to produce a slurry, which is then passed through a drying chamber to produce a Si3N4 tape. The Si3N4 tape is pressed and cut to produce a Si3N4 green sheet, which is then heat-treated at 600℃ for 12 hours to perform a degreasing process. The sheet is then sintered at 1850℃ and 1MPa in a nitrogen atmosphere using a gas pressure sintering method to produce a ceramic substrate (a) (silicon nitride Si3N4 substrate) of a predetermined size (190mm wide x 138mm long x 0.32mm thick).

[0110] Experimental example 1: Confirmation of production cost reduction

[0111] Ti (first deposition layer) and Ag (second deposition layer) were deposited in this order on the opposing upper and lower surfaces of the ceramic substrate of the manufacturing example. At this time, Ti was about 1.0 g / m 2 The Ag was evaporated at about 6.08 g / m 2 Two ceramic substrates (A) were prepared as described above, on both the upper and lower surfaces of which the first and second deposition layers were deposited, respectively.

[0112] In addition, two copper sheets measuring 270 mm x 190 mm x 0.3 mm were prepared.

[0113] One copper sheet was placed, and two ceramic substrates (A) were placed adjacent to each other so that there was as little gap between them as possible, and two ceramic substrates (A) were placed on one side of the copper sheet (at this time, two or more ceramic substrates (A) were placed parallel to each other on the copper sheet, and the deposition layer (Ag deposition layer) of each ceramic substrate (A) was placed in contact with the copper sheet), and the remaining copper sheet was placed on top of it in the same manner to manufacture a non-bonded laminate in the form of copper sheet / two ceramic substrates (A) (placed parallel to each other on the same plane) / copper sheet. At this time, the overlapping area between the two ceramic substrates and the copper sheet was about 90%.

[0114] Then, the laminate was heated for about 10 minutes in a hot press. -4 The treatment was carried out under a pressure of 15 MPa in a torr atmosphere at a temperature of 980°C. As a result, a sample was obtained in which the copper sheet and the silicon nitride substrate were bonded to each other: copper sheet / two ceramic substrates (A) (positioned parallel to one another on a plane) / copper sheet.

[0115] The sample was used to etch copper to manufacture copper circuits. Specifically, dry film was attached to both outer sides of the laminate, and then UV was irradiated onto the film to remove the film from the remaining areas except for the circuit areas, leaving only the areas where the copper should not be etched (circuit areas). The sample was then fed into an etching line to perform copper etching.

[0116] As a result, it was confirmed that etching the sample manufactured according to the present application (copper sheet / two ceramic substrates (A) (placed parallel to one another) / copper sheet) can reduce the time required to produce the same number of circuits by about half compared to etching two comparative samples (copper sheet / one ceramic substrate (A) / copper sheet) in which ceramic substrates are bonded one by one, and that more circuit substrate pieces can be produced in the same etching process time (e.g., an increase in production volume of about 30% or more). Thus, the present application has a significant cost-saving effect.

[0117] Experimental example 2: Evaluation of bonding strength

[0118] According to ASTM D6682, the bonding strength (N / mm) was measured for the test specimens of the following Examples 1 to 6 and Comparative Examples 1 to 6. Specifically, a sample of a copper sheet / silicon nitride substrate / copper sheet structure in which a copper sheet and a silicon nitride substrate were bonded to each other was etched to prepare a sample in which a copper strip with a width of 5 mm and a length of 100 mm was bonded to a ceramic substrate. Before the test, about 10 mm of the edge of the Cu strip was manually separated so that the Cu strip could be gripped by the grip of a universal testing machine (LS5 manufactured by Ametek). The test specimen was fixed to the universal testing machine, the Cu strip was gripped by the grip, and the stress on the grip was measured while separating at a speed of 50 mm / min, and the bonding strength was calculated.

[0119] The results are shown in Tables 1 to 3 below.

[0120] Example 1 (Ti deposition amount 1.076 g / m 2 , Ag deposition amount 4.005g / m 2 )

[0121] On the ceramic substrate of the manufacturing example, 0.0282 g of Ti was deposited for 70 seconds by sputtering to form a first deposition layer. Then, 0.105 g of Ag was deposited on the first layer for 30 seconds to form a second deposition layer. At this time, the formation area of ​​the first and second deposition layers was adjusted to be the same as that of the ceramic substrate (a) (190 mm wide x 138 mm long). Here, the deposition amount of Ti per unit area was 1.076 g / m 2 The deposition amount of Ag per unit area is 4.005 g / m 2 It is.

[0122] Two ceramic substrates (A) and two copper sheets (270mm wide x 185mm long x 0.3mm thick) were prepared as above. The two ceramic substrates (A) were placed adjacent to each other to minimize the gap between them, and the two ceramic substrates (A) were placed on one side of the prepared copper sheet (at this time, the two ceramic substrates (A) were placed parallel to each other on the copper sheet, and the deposition layer (second deposition layer containing Ag) of each ceramic substrate (A) was placed in contact with the copper sheet), and the remaining copper sheet was placed on top of them in the same manner to prepare a non-bonded laminate in the form of copper sheet / two ceramic substrates (A) (placed parallel to each other on the plane) / copper sheet. At this time, the overlapping area between the two ceramic substrates and the copper sheet was about 95%.

[0123] Thereafter, the laminate was -4 The mixture was hot pressed at a temperature of 980°C and a pressure of 15 MPa in a torr atmosphere.

[0124] Through the above series of steps, a test specimen was produced that included a Cu metal sheet, a TiN bonding layer, and Si3N4.

[0125] Example 2 (Ti deposition amount 1.194 g / m 2 , Ag deposition amount 4.005g / m 2 )

[0126] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0313 g of Ti was deposited to form the first layer. At this time, the deposition amount of Ti per unit area was 1.194 g / m 2 The deposition amount of Ag per unit area is 4.005 g / m 2 It is.

[0127] Example 3 (Ti deposition amount 1.030 g / m 2 , Ag deposition amount 5.339g / m 2 )

[0128] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0270 g of Ti was deposited to form the first layer, and 0.1400 g of Ag was deposited to form the second layer. At this time, the deposition amount of Ti per unit area was 1.030 g / m 2 The deposition amount of Ag per unit area is 5.339 g / m 2 It is.

[0129] Example 4 (Ti deposition amount 1.220 g / m 2 , Ag deposition amount 5.339g / m 2 )

[0130] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0320 g of Ti was deposited to form the first layer, and 0.1400 g of Ag was deposited to form the second layer. At this time, the deposition amount of Ti per unit area was 1.220 g / m 2 The deposition amount of Ag per unit area is 5.339 g / m 2 It is.

[0131] Example 5 (Ti deposition amount 1.003 g / m 2 , Ag deposition amount 4.005g / m 2 )

[0132] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0263 g of Ti was deposited to form the first layer. At this time, the deposition amount of Ti per unit area was 1.003 g / m 2 The deposition amount of Ag per unit area is 4.005 g / m 2 It is.

[0133] Example 6 (Ti deposition amount 0.961 g / m 2 , Ag deposition amount 4.005g / m 2 )

[0134] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0252 g of Ti was deposited to form the first layer. At this time, the deposition amount of Ti per unit area was 0.961 g / m 2 The deposition amount of Ag per unit area is 4.005 g / m 2 It is.

[0135] Comparative Example 1 (Ti deposition amount 0.374 g / m 2 , Ag deposition amount 2.868g / m 2 )

[0136] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0098 g of Ti was deposited to form the first layer, and 0.0752 g of Ag was deposited to form the second layer. At this time, the deposition amount of Ti per unit area was 0.374 g / m 2 The deposition amount of Ag per unit area is 2.868 g / m 2 It is.

[0137] Comparative Example 2 (Ti deposition amount 0.599 g / m 2 , Ag deposition amount 2.868g / m 2 )

[0138] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0157 g of Ti was deposited to form the first layer, and 0.0752 g of Ag was deposited to form the second layer. At this time, the deposition amount of Ti per unit area was 0.599 g / m 2 The deposition amount of Ag per unit area is 2.868 g / m 2 It is.

[0139] Comparative Example 3 (Ti deposition amount 0.843 g / m 2 , Ag deposition amount 2.868g / m 2 )

[0140] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0221 g of Ti was deposited to form the first layer, and 0.0752 g of Ag was deposited to form the second layer. At this time, the deposition amount of Ti per unit area was 0.843 g / m 2 The deposition amount of Ag per unit area is 2.868 g / m 2 It is.

[0141] Comparative Example 4 (Ti deposition amount 1.034 g / m 2 , Ag deposition amount 2.868g / m 2 )

[0142] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0342 g of Ti was deposited to form the first layer, and 0.0752 g of Ag was deposited to form the second layer. At this time, the deposition amount of Ti per unit area was 1.304 g / m 2 The deposition amount of Ag per unit area is 2.868 g / m 2 It is.

[0143] Comparative Example 5 (Ti deposition amount 1.041 g / m 2 , Ag deposition amount 6.808g / m 2 )

[0144] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0273 g of Ti was deposited to form the first layer, and 0.1785 g of Ag was deposited to form the second layer. At this time, the deposition amount of Ti per unit area was 1.041 g / m 2 The deposition amount of Ag per unit area is 6.808 g / m 2 It is.

[0145] Comparative Example 6 (Ti deposition amount 0.599 g / m 2 , Ag deposition amount 4.005g / m 2 )

[0146] A test piece including a Cu metal sheet, a TiN bonding layer, and a Si3N4 ceramic substrate was manufactured in the same manner as in Example 1, except that 0.0157 g of Ti was deposited to form the first layer. At this time, the deposition amount of Ti per unit area was 0.599 g / m 2 The deposition amount of Ag per unit area is 4.005 g / m 2 It is.

[0147] [Table 1]

[0148] [Table 2]

[0149] [Table 3]

[0150] First, comparing the test pieces of Examples 1 and 2 and Comparative Examples 1 to 4, the deposition amount of Ag per unit area was 3.50 g / m 2 The test pieces of Examples 1 and 2 showed excellent bonding strengths of 21.4 N / mm and 22.1 N / mm, respectively, but the deposition amount of Ag per unit area was 3.50 g / m 2 The test pieces of Comparative Examples 1 to 4, which are less than 7.5 N / mm, all showed low bonding strengths of 7.5 N / mm or less. In particular, although the amount of Ti deposited per unit area of ​​the test piece of Comparative Example 4 was higher than that of the test pieces of Examples 1 and 2, the test piece of Comparative Example 4 showed a much lower bonding strength due to its low Ag content. This is considered to be the result of the strength of the metal sheet changing (improving) depending on the amount of Ag deposited. Next, comparing the test pieces of Examples 1 and 3 and Comparative Example 5, there is no significant difference in the amount of Ti deposited per unit area. However, the amount of Ag deposited per unit area of ​​6.10 g / m 2The test pieces of Examples 1 and 3 below showed excellent adhesion strengths of 21.4 N / mm and 16.3 N / mm, respectively, while the test piece of Comparative Example 5 showed a decreased adhesion strength of 15.6 N / mm. This is believed to be due to the formation of Ag residue at the interface caused by excessive Ag deposition.

[0151] Next, comparing the test pieces of Examples 1, 2, 5, and 6 and Comparative Example 6, the deposition amount of Ag per unit area is almost the same. The deposition amount of Ti per unit area is 0.61 g / m 2 The test pieces of Examples 1, 2, 5, and 6 showed a minimum bonding strength of 9.4 N / mm or more, but the deposition amount of Ti per unit area was 0.61 g / m 2 The test piece of Comparative Example 6, which has a bonding strength of less than 8.6 N / mm, exhibited a low bonding strength of less than 8.6 N / mm. This is believed to be the result of the strength of the bonding layer changing (improving) depending on the amount of Ti deposition. In particular, when the amount of Ti deposition per unit area was 1.02 g / m 2 The test pieces of Examples 1 and 2 exhibited excellent bonding strengths of 21.4 N / mm and 22.1 N / mm, respectively.

[0152] Next, looking at the test pieces of Examples 1, 2, and 4, the deposition amount of Ti per unit area was 1.30 g / m 2 The test pieces of Examples 1, 2, and 4 below all showed excellent bonding strength of 20 N / mm or more. However, the deposition amount of Ti per unit area was 1.02 g / m 2 Above this level, it can be confirmed that the increase in the amount of Ti deposition is so small that the bonding strength reaches a saturation value. Therefore, in order to prevent the cost of raw materials from being wasted and to provide optimal bonding strength between the interfaces, the amount of Ti deposition per unit area is set to 1.30 g / m 2 It is preferable that:

Claims

1. a first step of preparing a ceramic substrate (a) having opposing upper and lower surfaces with areas SA, and forming deposition layers on the upper and lower surfaces of the ceramic substrate having the area SA, thereby manufacturing a ceramic substrate (A) having an upper deposition layer and a lower deposition layer formed on the opposing upper and lower surfaces, respectively; A second step of preparing an upper metal sheet (B) and a lower metal sheet (B') each having one side with an area SB that is 1.5 times larger than the area SA; a third step of arranging the metal sheets (B, B') and the two or more ceramic substrates (A) between the upper metal sheet (B) and the lower metal sheet (B') in the area SB facing each other, so that the two or more ceramic substrates (A) are positioned parallel to one another on a plane; and a fourth step of hot pressing the upper and lower metal sheets (B, B') to bond the metal sheets (B, B') to the ceramic substrate (A) via the upper and lower deposition layers.

2. 2. The method of claim 1, wherein the area SB of one side of the upper metal sheet (B) and the lower metal sheet (B') is 1.5 to 6.0 times larger than the area SA.

3. 2. The method of claim 1, wherein the area SB of one side of the upper metal sheet (B) and the lower metal sheet (B') is 1.5 to 2.5 times larger than the area SA.

4. The third step is 2. The method for manufacturing a printed circuit board according to claim 1, wherein the metal sheets (B, B') and the ceramic substrates (A) are arranged such that the overlapping area between one surface of the metal sheet (B, B') having the area SB and the two or more ceramic substrates (A) is 70% or more of the total area (ST=n×SA, n is a natural number of 2 or more and means the number of ceramic substrates located between the metal sheets (B, B')) of the ceramic substrates (A) located between the upper metal sheet (B) and the lower metal sheet (B').

5. 2. The method for manufacturing a printed circuit board according to claim 1, wherein the metal sheets (B, B') and the ceramic substrates (A) are arranged such that the overlapping area between one surface of the metal sheet (B, B') having the area SB and the two or more ceramic substrates (A) is 90% or more of the total area (ST=n×SA, n is a natural number of 2 or more and means the number of ceramic substrates located between the metal sheets (B, B')) of the ceramic substrates (A) located between the upper metal sheet (B) and the lower metal sheet (B').

6. The deposition layer includes Ag and Ti; The deposition amount of Ag per unit area is in the range of 3.50 to 6.10 g / m2, 2. The method for producing a printed circuit board according to claim 1, wherein the deposition amount of Ti per unit area is in the range of 0.61 to 1.30 g / m2.

7. 2. The method for producing a printed circuit board according to claim 1, wherein the hot pressing is carried out at a temperature of 450 to 1,300° C. while applying a pressure of 1 to 25 MPa.

8. 7. The method for producing a printed circuit board according to claim 6, wherein the deposition amount of Ag per unit area is in the range of 4.00 to 4.60 g / m2.

9. 7. The method for producing a printed circuit board according to claim 6, wherein the deposition amount of Ti per unit area is in the range of 1.02 to 1.30 g / m2.

10. 6. The method for producing a printed circuit board according to claim 5, wherein the deposition in the first step includes forming a first deposition layer containing Ti on each of the upper and lower surfaces of the ceramic substrate (a) and forming a second deposition layer containing Ag on the first deposition layer.

11. 2. The method for manufacturing a printed circuit board according to claim 1, wherein the ceramic substrate (a) comprises at least one of Si3N4, AlN, and Al2O3.

12. The method for manufacturing a printed circuit board according to claim 11, wherein the metal sheets (B, B') contain at least one of Cu, Al, Ni and Fe.

13. The method of claim 11, wherein the ceramic substrate comprises one or more of Si3N4 and AlN.

14. The hot pressing causes a material contained in the deposition layer to react with a material contained in the ceramic substrate to form a bonding layer; The method for manufacturing a printed circuit board according to claim 12 , wherein the bonding layer contains at least TiN.

15. The method for manufacturing a printed circuit board according to claim 1, further comprising the step of etching the metal sheets (B, B').

Citation Information

Patent Citations

  • Method for manufacturing ceramic metal substrates

    JP2006527666A

  • Ceramics original plate for manufacturing power module and multilayer substrate for manufacturing power module

    JP2014204031A

  • Manufacturing method of substrate for power module

    JP2018137396A